2017
DOI: 10.21608/pssjn.2017.33071
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Occupational Hazards at Textile Factory in Damietta City

Abstract: Background: Occupational hazards that exist within the textile factory have a destructive and serious effect on the workers' health. The aim: of this study is to assess the workers' occupational health hazards at textile factory in Damietta City. Sample: the study is carried on 108 workers. Research design: A descriptive research design is utilized. Data collection tools: data are collected using two tools: workers' structured Interview Questionnaire, and workers' Observational Checklist. Results: revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Regarding the distribution of nose and eye symptoms among the studied workers. The findings of our study are consistent with those of Ibrahim (20), who observed a high prevalence of health issues resulting from exposure to chemical hazards. Specifically, the majority (81.3%) of the participants in their study experienced health problems, with respiratory tract diseases being the most prevalent (96.7%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding the distribution of nose and eye symptoms among the studied workers. The findings of our study are consistent with those of Ibrahim (20), who observed a high prevalence of health issues resulting from exposure to chemical hazards. Specifically, the majority (81.3%) of the participants in their study experienced health problems, with respiratory tract diseases being the most prevalent (96.7%).…”
Section: Discussionsupporting
confidence: 92%
“…The main results of this study were Regarding sociodemographic data, our findings align with the research conducted by Ibrahim [20] . Ibrahim's study focused on a textile factory located in Damietta city, which encompasses three major wards: pretreatment and Fiber preparation wards, Spinning and weaving wards, and dyeing and printing wards.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Table (9) shows that the positive aspect of psychological factors were more frequent among non exposed workers with statistical significant difference between exposed and non exposed groups (p<0.05). Table (10) shows that only 22.9% of the exposed workers were satisfied with the presence of sufficient space for routine work activities while most of workers (82%) were satisfied with the enough leg and foot space available while sitting and standing. Only 46.3% of the workers have chairs with a back rest.…”
Section: Resultsmentioning
confidence: 99%